
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.


a) \(A=x^2-2xy+y^2+3x-3y-4\)
\(=\left(x-y\right)^2-1+3x-3y-3\)
\(=\left(x-y-1\right)\left(x-y+1\right)+3\left(x-y-1\right)\)
\(=\left(x-y-1\right)\left(x-y+1+3\right)\)
\(=\left(x-y-1\right)\left(x-y+4\right)\)

\(x^2-2xy+y^2+3x-3y-10=\left(x^2-2xy+y^2\right)+3\left(x-y\right)-10=\left(x-y\right)^2+3\left(x-y\right)-10=\left(x-y\right)^2-2\left(x-y\right)+5\left(x-y\right)-10=\left(x-y\right)\left(x-y-2\right)+5\left(x-y-2\right)=\left(x-y+5\right)\left(x-y-2\right)\)
= ( x - y)^2 - 3 ( x - y) . -10
= ( x - y)^2 - 2.(x-y) . 3/2 +9/4 - 49/4
= ( x - y - 3/2) ^2 - (7/2)^2
= ( x- y - 3/2 - 7/2 )( x - y -3/2 + 7/2 )
=( x - y - 5 )( x - y + 2)

\(x^2-2xy+y^2+3x-3y-10\)
\(=\left(y^2-xy-5y\right)-\left(xy-x^2-5x\right)+\left(2y-2x-10\right)\)
\(=y\left(y-x-5\right)-x\left(y-x-5\right)+2\left(y-x-5\right)\)
\(=\left(y-x+2\right)\left(y-x-5\right)\)


= ( x - y)^2 - 3 ( x - y) . -10
= ( x - y)^2 - 2.(x-y) . 3/2 +9/4 - 49/4
= ( x - y - 3/2) ^2 - (7/2)^2
= ( x- y - 3/2 - 7/2 )( x - y -3/2 + 7/2 )
=( x - y - 5 )( x - y + 2)
LÀm thế này đúng không cho nhận xét

\(-y^2+2xy-x^2+3x-3y\)
\(=-\left(x^2-2xy+y^2\right)+3\left(x-y\right)\)
\(=-\left(x-y\right)^2+3\left(x-y\right)\)
\(=\left(x-y\right)\left(-x+y+3\right)\)

\(x^2-3x+xy-3y\)
\(=x\left(x+y\right)-3\left(x+y\right)\)
\(=\left(x+y\right)\left(x-3\right)\)
\(x^2-2xy+y^2-4=\left(x-y\right)^2-2^2=\left(x-y-2\right)\left(x-y+2\right)\)
\(x^2+x-y^2+y=\left(x-y\right)\left(x+y\right)+\left(x+y\right)=\left(x+y\right)\left(x-y+1\right)\)

Bài làm
a, x2 - 3x + xy - 3y
= x(x - 3) + y(x - 3)
= (x - 3)(x + y)
b, x2 + y2 - 2xy - 25
= (x2 - 2xy + y2) - 25
= (x + y)2 - 25
= (x + y + 5)(x + y - 5)
Sửa đề: \(x^2-2xy+y^2+3x-3y-10\)
\(=\left(x-y\right)^2+3\left(x-y\right)-10\)
\(=\left(x-y\right)\left(x-y+3\right)-10\)
Đặt \(x-y=t\)
\(\Rightarrow t.\left(t+3\right)-10\)
\(=t^2+3t-10\)
\(=t^2+5t-2t-10\)
\(=t\left(t+5\right)-2\left(t+5\right)\)
\(=\left(t+5\right)\left(t-2\right)\)
\(=\left(x-y+5\right)\left(x-y-2\right)\)